Description and Consistency of In-Game Pitching Kinetics’ Relationship With Ball Velocity - Giordano, Kevin; Nebel, Adam R; Lerch, Benjamin; Oliver, Gretchen D (International Journal of Sports Medicine, 2025)
Baseball pitchers commonly suffer shoulder and elbow injuries. Previous research on the relationship between pitch velocity and upper extremity kinetics has been limited to laboratory settings, but recent strides in markerless motion capture have allowed analysis of in-game baseball pitching biomechanics. Therefore, our purpose was to provide normative data of in-game pitching kinetics and assess the relationships between pitch velocity and shoulder and elbow kinetics. Data from 183 college pitchers were included in this retrospective analysis of in-game college baseball games. Multilevel models were used to assess the relationships between pitch velocity and kinetics. Intraclass correlation coefficients were used to assess the intrapitcher relationship between kinetics across multiple outings. The inclusion of random slopes did not meaningfully reduce intrapitcher throwing arm kinetic variance. Additionally, the intrapitcher relationship between throwing arm kinetics and ball velocity did not remain constant across multiple outings. Pitch velocity and in-game throwing arm kinetics did not have a strong intrapitcher relationship, which is different than the results of previous laboratory analyses. The intrapitcher relationship between fastball velocity and throwing arm kinetics does not remain consistent across multiple outings. Additionally, this study provides normative in-game kinetic data for baseball pitching.
Keywords: Biomechanics; Injury; Markerless motion capture; Multi-level model